Tribological Behavior of Hafnium Diboride Based Material. Issue 3 (2nd July 2020) - Sonber, Jitendra Kumar; Majumdar, Sanjib; Singh, Kulwant; Kain, Vivekanand
Abstract : Tribological behavior of hot pressed HfB2 -5%TiSi2 composite was studied under reciprocative sliding condition using cemented tungsten carbide (WC-Co) ball as counter body. Coefficient of friction (COF) for HfB2 composite sample was obtained in the range of 0.43 to 0.63 at different loads. It was observed that enhancement of load from 5 to 15 N resulted in decrease of COF of HfB2 . Specific wear rate of HfB2 composite was evaluated in the order of 10 –6 mm 3 /N.m. Microstructures of wear scar revealed that tribochemical layer was formed on the worn surface of HfB2 (flat). GRAPHICAL ABSTRACT: